Modeling and preliminary analysis of a miniaturized rotary motor driven by single piezoelectric stack actuator. (July 2016) - Liu, Weiting; Zhou, Maoying; Stefanini, Cesare; Fu, Xin
This paper presents a compact motor (6 mm in diameter) with a single piezoelectric stack actuator and a frame structured stator, which works under the principle of natural inchworms. Preliminary motion analysis and dynamic modeling are conducted based on the assumption of structural rigidity. The prototype can generate output torque of about 279 nNm and speed up to 200 rpm with a power input of 60 Vpp at the frequency of 12.7 kHz. In addition, rotational concentricity of the motor is discussed via analyzing captured video of the operating motor. Compared with the previous prototype that is 17 mm in diameter, the simplicity of the motor structure provides an effective miniaturization solution, which is important to many applications such as medical instruments and consumer electronics.